Cek Gula, Cek BMI, Cegah Diabetes: Implementasi Program Pengabdian Masyarakat dalam Pencegahan Penyakit Tidak Menular - Trisakti Halimah Delimasari; Annisa’ Arifatul Hikmah; Elsa Tursina; Riska Fajar Fathony; Muhammad Yusuf (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to increase public awareness and the ability to detect diabetes risk early through blood glucose level checks, Body Mass Index (BMI) measurements, health education, and mentoring healthy behavior changes. The approach used included initial assessments, building communication with residents, forming support groups, implementing education, and program evaluation. A total of 30 participants participated in the screening activity. The results showed that 66.67% were in the age group ≤55 years and 80.00% were female. Based on nutritional status, 43.33% of participants were obese and 26.67% were overweight. Blood pressure checks showed 36.67% had hypertension, while 40.00% had high blood glucose levels. These findings illustrate the high prevalence of modifiable risk factors in the community. The implementation of education was proven to increase participants' understanding of diet management, physical activity, and the importance of routine screening, as demonstrated by active involvement and positive responses from participants.